The Role of Spiritual Mindfulness Therapy in Increasing Self-Confidence Among Adolescent - Rahmawati, Ashri Maulida; Jauhar, Muhamad; Masithoh, Anny Rosiana; Pusparatri, Edita (Indonesian Journal of Health Research and Development, 2024)
This study aimed to determine the influence of spiritual Mindfulness on increasing adolescent self-confidence. Evaluating the benefits of spiritual therapies such as mindfulness for the mental health of adolescents is highly needed. Adolescence is difficult to adjust to and is especially susceptible to declining self-confidence. Low self-confidence causes most adolescent crises in the current school system. Spiritual Mindfulness is an easy-to-use strategy that can help adolescents become aware of their problems without passing judgment, which reduces costs and saves time. The study design was a pre-experiment with a pre and post-test with the control group. In purposive sampling, the intervention and control students chose twenty-six respondents from senior high school students in Kudus. The research instrument used in this study was the Student Self-Confidence Questionnaire. The researcher conducted six 30-minute sessions of spiritual mindfulness therapy over two days. Research results showed the difference in self-confidence scores before and after the intervention in the intervention group was found statistically significant with a p-value of 0.013 (p < 0.05) and in the control group with a p-value of 0.000 (p < 0.05). The effect of spiritual mindfulness therapy on self-confidence was not statistically significant, with a p-value of 0.110 (p> 0.05). So, it can be concluded that Spiritual mindfulness therapy has no significant influence on self-confidence. The way spiritual mindfulness therapy is given to teenagers needs to be altered to see more noticeable improvements in self-confidence.